Analisis Faktor-Faktor yang Mempengaruhi Keterandalan Pelaporan Keuangan Pemerintah Daerah Kabupaten Temanggung - Sari, Puput Novita; , Dr. Zulfikar, SE, M.Si (2017)
The purpose of this study was to determine the effect of human resource capacities, appropriate internal control, information technology utilization, local of financial monitoring, implementation of government accounting standards, information asymmetry, and commitmen organization of local government financial reporting reliability at Temanggung Regency. The used sampling method is purposive sampling. Data collection is done by giving as many as 83 copies of the questionnaire, which was distributed to respondents at DPPKAD of Temanggung Regency. The data obtained are than analyzed using SPSS 21.00. Based on the analysis result, obtained that the human resource capacities, appropriate internal control, information technology utilization, local of financial monitoring, implementation of government accounting standards, information asymmetry, and commitmen organization has significant effect to local government financial reporting reliability at DPPKAD of Temanggung Regency. Keywords: human resource capacities, appropriate internal control, information technology utilization, local of financial monitoring, implementation of government accounting standards, information asymmetry, commitmen organization, local government financial reporting reliability.